JAPANESE LANGUAGE TRAINING FOR HOSPITALITY EMPLOYEES OF SHERATON BANDUNG HOTEL & TOWERS - Rahardjo, Hardianto; Kuraesin, Uning; Ariestafuri, Nurza; Tresnasari, Ningrum; Novitasari, Raden (LPPM Univ. Ibn Khaldun Bogor, 2025)
Good communication skills are a key factor in ensuring excellent service in the hospitality industry. In the context of international tourism, foreign language proficiency is essential, given that guests are not limited to domestic visitors. Effective communication with foreign guests, particularly those from Japan, is a crucial concern. In reality, many hotel staff still struggle to interact with Japanese guests due to limited Japanese language proficiency, while English is often ineffective due to pronunciation differences. Given these conditions, the Japanese Language Study Program at Universitas Widyatama conducted a community service activity in the form of basic Japanese language training for hotel staff. This training focused on vocabulary and formal sentences relevant to the hospitality industry. In addition to improving employee communication skills, this activity also aimed to make an academic contribution to improving the quality of the tourism workforce and serving as a concrete manifestation of the Tridharma Perguruan Tinggi (Three Pillars of Higher Education).